Retracted: Study on measurement reliability based on Liu estimator. (31st May 2018) - Huang, Jiewu; Ma, Lie; Li, Rong
Abstract: Retraction: Huang J, Ma L, Li R. Study on measurement reliability based on Liu estimator. Concurrency Computat Pract Exper . 2019;31:e4709.https://doi.org/10.1002/cpe.4709 The above article, published online on 31st May 2018 in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the authors, the journal Editor, Professor Geoffrey Fox, and John Wiley and Sons Ltd. The retraction has been agreed due to a reversal of the Liu and OLS estimators resulting in foundational errors that are beyond the scope of an erratum.